Enhanced Multiplexing of Immunofluorescence Microscopy Using a Long‐Stokes‐Shift Fluorophore. Issue 8 (13th August 2021) - Reitz, Sydney J.; Sauerbeck, Andrew D.; Kummer, Terrance T.
Abstract: Immunofluorescence labeling and microscopy offer a highly specific means to visualize proteins or other molecular species in a sample by labeling target antigens with fluorescent probes. These fluorescent probes can then be visualized using a fluorescence microscope, allowing their relative spatial relationships to be determined. Due to spectral overlap of common fluorophores, however, it can be challenging to analyze more than three antigens in a single sample with standard imaging approaches. This article describes multiplexed labeling and imaging of four target antigens through the use of a long‐Stokes‐shift fluorophore—a fluorophore with an unusually large gap between its excitation and emission maxima—in tandem with three conventional fluorophores. This combination allows for multiplexed imaging of four antigens in a single sample with excellent spectral discrimination suitable for sensitive analyses using standard imaging hardware. Particular advantages of this approach are its flexibility in terms of target antigens and the lack of any specialized procedures, reagents, or equipment beyond the commercially available labeling reagent coupled to the long‐Stokes‐shift fluorophore. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Four‐probe immunofluorescence labeling Basic Protocol 2 : Four‐probe immunofluorescence imaging